The Interrelationship of The Covid-19 Pandemic with Alcohol Abuse (Eurasian Medical Research Periodical, 2022)
The COVID-19 pandemic has caused the worst health problem in the world. In response, many countries have adopted disease control measures. These measures have an involuntary negative impact on the mental health and psyche of the population. Longterm social isolation is associated with alcohol consumption and misuse, leading to a potential health crisis. This study focuses on the role of external factors and changes in mental health in alcohol abuse during the COVID-19 pandemic.